2014
DOI: 10.1259/bjr.20140017
|View full text |Cite
|
Sign up to set email alerts
|

Efficient visual-search model observers for PET

Abstract: Objective: Scanning model observers have been efficiently applied as a research tool to predict human-observer performance in F-18 positron emission tomography (PET). We investigated whether a visual-search (VS) observer could provide more reliable predictions with comparable efficiency. Methods: Simulated two-dimensional images of a digital phantom featuring tumours in the liver, lungs and background soft tissue were prepared in coronal, sagittal and transverse display formats. A localization receiver operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Overall, the VS paradigm offers considerable advantages for analyzing detection-localization tasks, with several studies having shown improved stability compared to scanning models in situations where organ-boundary artifacts interfered with detection. 37 There were strong limited-angle artifacts at the borders of the fibroglandular compartment in some of the test images, and while some effort was made to control their impact on the feature extraction, this was not completely successful.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the VS paradigm offers considerable advantages for analyzing detection-localization tasks, with several studies having shown improved stability compared to scanning models in situations where organ-boundary artifacts interfered with detection. 37 There were strong limited-angle artifacts at the borders of the fibroglandular compartment in some of the test images, and while some effort was made to control their impact on the feature extraction, this was not completely successful.…”
Section: Discussionmentioning
confidence: 99%
“…Localization concordance is a more-stringent measure of agreement utilized in previous studies [26]. On the whole, it is reasonable to expect that the VS observer should improve concordance with humans when compared with scanning observers, as the initial hot-blob search is predicated on a basic tenet that humans understand about lesion detection for much of nuclear medicine.…”
Section: Discussionmentioning
confidence: 99%
“…A less-efficient gradient-ascent segmentation method yielded similar results in previous VS observer studies. 4 With the watershed algorithm, a 2-D test image is viewed as a topographic landscape with holes at the local minima. 13 When the landscape is lowered into a tank of water, water starts to fill the "catchment basins" around the holes.…”
Section: Model-observer Specificationsmentioning
confidence: 99%
“…3,4 These models perform distinct target search and analysis procedures, thereby simulating the visual-search (VS) process that trained radiologists engage in to interpret medical images. 5 Our VS model observer applies a feature-guided search that identifies target-like structure for subsequent analysis.…”
Section: Introductionmentioning
confidence: 99%